2022
DOI: 10.1007/s00501-022-01220-8
|View full text |Cite
|
Sign up to set email alerts
|

Forschungsdimension der European University on Responsible Consumption and Production – EURECA-PRO

Abstract: ZusammenfassungGlobale Umweltveränderungen, die dem technischen Fortschritt, der wachsenden Bevölkerung, der wachsenden Wirtschaft und dem daraus resultierenden Verlangen nach immer mehr Ressourcen geschuldet sind, wirken auf die natürlichen Regelkreise die das Ökosystem Erde steuern ein. Die zukünftige Vermeidung der Überbeanspruchung der Umwelt stellt eine der größten Herausforderungen dar, die die Menschheit zu lösen hat. Durch die Unterzeichnung der Pariser Klimaziele sowie der Sustainable Development Goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Lighthouse Research Missions regarding sustainable consumption and production [7] are established in all relevant disciplines, and cross-institutional research groups already yield promising research results that flow into the practical education of the ESt programme. Each participating university focuses on their expertise areas to achieve complementarity and an enhanced level of interdisciplinary research results.…”
Section: The European University Alliance Eureca-promentioning
confidence: 99%
“…Lighthouse Research Missions regarding sustainable consumption and production [7] are established in all relevant disciplines, and cross-institutional research groups already yield promising research results that flow into the practical education of the ESt programme. Each participating university focuses on their expertise areas to achieve complementarity and an enhanced level of interdisciplinary research results.…”
Section: The European University Alliance Eureca-promentioning
confidence: 99%
“…For this purpose, additional PBL training for lecturers and students is offered. Moreover, research results are incorporated into EURECA-PRO curricula through problem-based learning and the open access/science approach held by all alliance members ensures that all developed content is available globally and free of charge [13].…”
Section: Educationmentioning
confidence: 99%
“…In total, 488 research projects covering 805 SDG12 research topics have been identified. Through data analysis, EURECA-PRO has determined five research Lighthouse Missions that will significantly influence its research agenda in the coming years [13].…”
Section: Researchmentioning
confidence: 99%